The effects of block training on pacing during 20-km cycling time trial - Pereira Costa, V.; Antonacci Guglielmo, L. G.; Paton, C. D. (Applied Physiology, Nutrition, and Metabolism, 2017)
The aim of this study was to determine the effects of block training (BL) on pacing during a 20-km hilly cycling time trial (TT) in trained cyclists. Twenty male cyclists were separated into 2 groups: control and BL. The training of each cyclist was monitored during a period of 3 weeks. In the first week cyclists performed an overload period of 7 consecutive days of high-intensity interval training followed by 2 weeks of normal training. Cyclists performed 1 TT before intervention and 2 TT after 7 and 14 days at the end of training. Each training session consisted of 10 sets of 3 repeated maximal-effort sprints (15, 30, and 45 s) with an effort/recovery duration ratio of 1:5. The main finding of this study was that the power output displayed a significantly higher start from the start until the halfway point of the TT (p < 0.05). Additionally, power output was characterized by a significant higher end spurt in the final 2 km in the BL after 2 weeks at the end of training (p < 0.05). In addition, after 2 weeks at the end of the overload period the distribution of cadence was significantly lower throughout the TT (p < 0.01). Therefore, a short period of consecutive days of intense training enhances cycling performance and changes the power output in the beginning and final part of the TT in trained cyclists.